Predictores de progresión de enfermedad renal crónica en pacientes del Hospital Regional Isidro Ayora de Loja - Bravo Guamán, Paulina Cecibel (2020)
Chronic kidney disease (CKD) constitutes a global public health threat, and according to its natural history develops towards advanced stages, however, the prior detection of factors that accelerate this evolution would help to intervene and reduce the risk of progression, therefore, the present investigation was carried out, whose objective was to determine the predictive factors associated with the progression of chronic kidney disease in patients cared in the Hemodialysis Area of Hospital Regional Isidro Ayora de Loja. A descriptive, retrospective and quantitative approach study was carried out in 72 patients attended during the period September - December 2018. The information was gotten by analyzing the medical records and was recorded in a data collection sheet. In this study, 59.7% of patients with CKD were male, of all of them, the most affected age group with 47.2% between 45 and 64 years old, and progression of kidney disease occurred in 63,9% of patients. Regarding the associated risk factors, 52.8% of body mass index 25 kg/m2; 44.4% had arterial hypertension and concomitant diabetes mellitus, also anemia was found in 73.61% and hyperglycemia in 51.39% with a basal average of 145.13 mg/dl. In conclusion, the main factors associated with the progression of CKD in our environment are the high body mass index, hyperglycemia, arterial hypertension and diabetes mellitus. Key words: risk factors, kidney progression, hyperglycemia.